Implications of Force Majeure Conditions in the Power Purchase Agreement Carried out by PT PLN Persero in Connection with the Covid-19 Pandemic - Nurwahyudin, Dindin Syarief; Gunarto, Gunarto (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2022)
Provisions for the establishment of a national disaster due to Covid-19 require residents to limit business activities and daily activities. Communities are required to carry out independent isolation and keep their distance to prevent the transmission of Covid-19. These activity restrictions are referred to as Large-Scale Social Restrictions (PSBB). This situation creates difficult economic conditions for PT PLN Persero as a state company so that it can cause PT PLN Persero to be unable to fulfill its rights and obligations regarding the electricity purchase agreement entered into between PT PLN Persero and private companies. The type of research used is sociological juridical research. The methodology used in this research is descriptive analytical method with an interdisciplinary approach. The results of the study show that difficult conditions due to Covid-19 can be categorized as a Force Majeure situation as stated in the electricity sale and purchase agreement between PT PLN Persero and a private company. Force Majeure or Force Majeure Conditions are interpreted in several articles in the Civil Code, where the concept of force majeure, Force Majeure KAHAR or Force Majeure (in this case called the Force Majeure Condition) is found in several articles, namely Article 1244 of the Civil Code.Keywords: Agreement; Buy; Covid-19; Electricity; Sell.